AB0856 Quantitative Proteomics (Itraq) Reveals Putative Biomarkers in Pre-Radiological Osteoarthritis. (9th June 2015) - Mateos, J.; Fernández-Puente, P.; Relaño, S.; Rego-Pérez, I.; Oreiro, N.; Fernández-Lόpez, C.; Ruiz-Romero, C.; Blanco-García, F.
Abstract : Background: Osteoarthritis (OA) is the most common rheumatic disease and the major cause of pain and disability along the aging population globally (1, 2, 3). Recently, a panel of experts of the EULAR outlined the priority research needs for the near future, including the search for predictors of OA progression [4, 5]. Objectives: The identification in serum of a panel of early indicators or biomarkers to predict the pathology in pre-radiological stages but also for its handling and the developing of trials of treatment in radiological stages. Methods: 15 individual samples for each condition (OA Grade 0, pre-radiological stage Grade I, and radiological stage grades II-III and IV) were pooled in three groups with the aim of reducing the individual extreme values. After enrichment in the low-abundant protein fraction, the pooled samples were subjected to iTRAQ labelling and relative quantitative analysis was done using a 4800 MALDI-TOF/TOF platform (ABSciex). Results: We have detected two big sets of serum proteins modulated in the early pre-radiological OA process. Levels of apolipoproteins (apoE: ratio GI/G0=2.25; apoB-100: ratio GI/G0=2.01; apoA-IV: ratio GI/G0=1.99) are altered when comparing Grade I vs. Grade 0. Furthermore, up to six components of the complement, a group of proteins involved in immune response and inflammation are decreased in serum in early OA grades. Among them, complement component 5 -C5-, that have been recently identified as key player of the OA process (6), is much less abundant in any OA grade in comparison to Grade 0 (ratio GI/G0=0.35). Conclusions: Our results indicate that early pathological grades of the OA process are linked to an imbalance in the metabolism and, specifically, in the lipid metabolism. Altered serum levels of apo-lipoproteins and C5 could be used, in combination with other "dry" biomarkers, as an indicator for early OA process and to detect the pathology in pre-radiological stages. References: Tonge DP, Pearson MJ, Jones SW (2014). Osteoarthritis Cartilage. Mobasheri A (2013) Curr Rheumatol Rep 15: 385. Jotanovic Z, Mihelic R, Sestan B, Dembic Z (2014) Curr Drug Targets. Conaghan PG, Kloppenburg M, Schett G, Bijlsma JW, committee oboaEoah (2014) Ann Rheum Dis. Lotz M, Martel-Pelletier J, Christiansen C, Brandi ML, Bruyère O, et al. (2013) Ann Rheum Dis 72: 1756-1763. Wang Q et al. (2011) Nat Med. Nov 6;17(12):1674-9. Acknowledgements: We would like to thank to all the members of the Proteored network for scientific discussion and helpful suggestions and to the patients for the donation of the serum samples. Disclosure of Interest: None declared